174 Effects of high degree deacetylated chitosan supplementation on yolk and blood immune status of laying hens. (7th December 2018) - Farivar, A; Saber, N; Şahan, Z; Serbester, U; Yenilmez, F; Küçükgülmez, A; Kadak, A; Çelik, M; Tekeli, A; Kutlu, H; Celik, L
Abstract: Chitosan is a bioactive polymer obtained from marine crustaceans and is used as an immunomodulatory. To our knowledge, limited research has been published on the effect of dietary chitosan on the immune system of poultry. Therefore, this study was conducted to evaluate whether dietary chitosan with high degree of deacetylation (HDAC; minimum 90%) would affect on yolk and blood immune status of laying hens. Thirty four weeks old layers were divided into 5 dietary groups of similar mean body weight and mean egg weight, comprising 14 birds each. The birds were fed standard layer diets containing 0, 200, 400, 800 and 1600 ppm HDAC for 8 weeks period. The birds were housed in individual cages in a complete randomized design. The data were analysed using the General Linear Models (GLM) and linear, quadratic and cubic effects were determined by orthogonal polynomial contrasts of SAS (2000).A 16:8 hours light:dark photoperiod was employed. Feed and water were given ad libitum. The results showed that HDAC supplementation decreased linearly (P<0.05) yolk oxidant capacity of eggs. The plasma antioxidant capacity was increased linearly and cubically by dietary chitosan levels. It could be concluded that providing dietary HDAC chitosan, which is produced from marine crustacean shell as a waste product of seafood industry, have promising potential to decrease yolk oxidant capacity of laying hens regardless of the supplementation levels. Also, the plasma antioxidant capacity were improved by dietary chitosan supplementation. Chitosan has the potential to improve the immune status.